6 and 14 Hz Positive Spikes on Scalp Electroencephalogram - Sanariya, Kalpesh; Garg, Arun; More, Aniruddha; Bansal, Atma Ram (International Journal of Epilepsy, 2018)
Benign epileptiform variants (BEVs) are often noted in routine electroencephalogram (EEG) monitoring and are sometimes misinterpreted as epileptiform discharges. Six and 14 Hz positive spikes are one of such BEVs seen especially in children. However, these variants can also be seen in intensive care unit EEG recordings. Here, we have reviewed the history and electrical details of these 6 and 14 Hz variants with their clinical significance.
Keywords: EEG; benign epileptiform variants; 6 and 14 Hz